Comportamiento agronómico y productivo en tres variedades de col (Brassica oleracea v.), con tres tipos de abonos orgánicos, en la parroquia San Simón, provincia Bolívar - Bayas Lorenty, Luis Alexander (2023)
The present research work was developed to evaluate the "Agronomic and productive behavior in three varieties of cabbage (Brassica Oleracea V.) with three types of organic fertilizers, in the San Simón parish, Bolívar province". The objectives of this research were based on the agronomic characterization of the cabbage crop, the efficiency of organic fertilizers and the yield of cabbage varieties. The treatments under study were for the FA (cabbage varieties) and the FB (organic fertilizers) the same ones that were established in a DBCA with a 3*4*3 factorial arrangement with 12 treatments, 3 repetitions and 36 experimental units, all Data obtained from this test were submitted to a statistical study assessed by Tukey's test at 5%. The results obtained for the qualitative cabbage size variable showed that 44.44% of the crop produced medium-sized cabbages. The analysis of variance determined that the twelve treatments had significant differences in the variables plant height (AP), number of leaves per plant (NH), stem diameter (DT), days to cabbage formation (DFR), diameter of the cabbage (DR), Days to harvest (DC), Mortality percentage (PM), Incidence of pests and diseases (IPE), Weight in Kg per plot (PKg/P), Yield Kg per ha (RKg/ha), while the variables taking percentage (PP) and number of cabbages per plot (NRP) did not obtain significant differences, being the only parameters that behaved equally. The statistical results showed that the yield of the cabbage varieties depended significantly on the type of organic fertilizer applied, with T7 (cabbage + chicken manure) and T6 (cabbage + bokashi) presenting the highest yield values with 62520.83 kg/ha. and 60466.67 kg/ha respectively, recording the control treatments with the lowest yields. The agronomic characters that contributed to the yield were Plant height (AP), stem diameter (T), cabbage diameter (DR) and weight in kg per plot (Pkg/P). In the cost- benefit analysis, it was confirmed that the variety of cabbage + chicken manure was the best treatment with a profit of $1.04, as was cabbage + worm humus with a B/C of $1.01. Keywords: v